Right ventricular diastolic dysfunction in the postoperative period of tetralogy of Fallot - Cardoso,Silvia Meyer (2003)
OBJECTIVE: To assess right ventricular diastolic function in the intermediate postoperative period of repair of tetralogy of Fallot. METHODS: We carried out a case-control study with 60 patients divided into 2 groups as follows: 1) group I - 30 patients who had undergone repair of tetralogy of Fallot and 2) group II - 30 healthy children. The 2 groups were paired for age, sex, and body surface. The flows in the pulmonary and tricuspid valves were analyzed with Doppler echocardiography. The presence of anterograde flow at the end of diastole in the pulmonary artery defined restrictive right ventricular physiology. Surgical, radiological, electrocardiographic, and echocardiographic variables were analized in the group I. RESULTS: The velocity of the A wave and the E/A ratio for the tricuspid valve showed significant differences between the groups. Cases with E/A < 1.30 predominated in inspiration (group I - 19/30, and group II - 5/30). The duration of the QRS complex on the electrocardiogram was significantly increased in patients with E/A <1.30. Nineteen (63.3%) patients had restrictive right ventricular physiology, which had a longer postoperative period, longer duration of the QRS complex, and a lower E/A ratio in inspiration. The surgical and radiological variables showed no statistical difference. CONCLUSION: Restrictive right ventricular physiology was detected on the intermediate follow-up of most patients undergoing repair of tetralogy of Fallot. The postoperative period and QRS duration were increased in patients with impairment in diastolic function.